The custom-made foot orthosis using the Central Stabilizer Element: nex concept of element - Gijón-Noguerón, Gabriel; Ortega-Ávila, Ana Belén; Montes-Alguacil, Jesús; Ruiz-Muñoz, María (My University, 2019)
Foot orthoses have been applied for the management of lower limb disorders, mainly for those who develop foot pain. The Central Stabilizer Element (CSE) is a new element that contains the midfoot laterally when a plantar insole is manufactured. OBJECTIVES: - To determine the effect on foot pain of adding the Central Stabilizer Element during the manufacturing process of foot orthosis, -- - To describe the proportions of Central Stabilizer Element in terms of width and length of this element. METHODS: A sample comprising 130 patients (57 males and 73 females) with foot pain was recruited for this study, with the patients having supinated, neutral, pronated and overpronated feet. All the patients received a custom-made foot orthosis with the Central Stabilizer Element. The Central Stabilizer Element was made of resins of polyvinyl chloride, and is a device insert in foot orthosis that contains the midfoot laterally to control pronation and supination movements. Conclusion •The students know how to design the insole. •They know how to match different foot posture with the different types of insoles •We make our decisions based on the scientific evidence found
Keywords: Podología; Pies - Enfermedades; Foot orthoses; Foot; Pain